Oral symptoms and oral health in patients with chronic kidney disease - Maria Auxiliadora Gomes do NASCIMENTO; Maria Sueli Marques SOARES; Eduardo CHIMENOS KÜSTNER; Dasaiev Monteiro DUTRA; Raquel Lopes CAVALCANTI (Faculdade São Leopoldo Mandic, 2018)
Objective: Chronic kidney disease is characterized by progressive and irreversible loss of kidney function. The impact of this disease on oral health also presents controversial results. The aim of the study was to determine oral health conditions and oral symptoms of patients with Chronic kidney disease undergoing hemodialysis. Methods: A cross-sectional study on a population with chronic renal failure was performed. Anamnesis and oral examination, decayed, miss and filled teeth (DMFT) index, community periodontal index, simplified oral hygiene index (OHI-S) and gingival index were conducted. Data were processed using SPSS v.s. 20.0 using descriptive statistics and Fischer's exact test and ANOVA test (p<0.05). Results: 64.9% of all the individuals were male. The mean age was 50.7±14.8 years. 82.4% had symptoms oral while 44.6% had xerostomia and 31.1% dysgeusia. The mean DMFT was 20.49+8.68, the GI was low in 78.4% and the OHI-S was satisfactory in 73%; according to the community periodontal index, the presence of dental calculus occurred in 52.7%, periodontal pockets 41.9% and gingivitis 2.7%. There was a statistically significant association between xerostomia (p=0.017) and number of drugs consumed and between dysgeusia and OHI-S (p=0.011). Conclusion: The results suggest that oral symptoms such as dry mouth and dysgeusia, are common in Chronic kidney disease patients undergoing hemodialysis. Dental calculus and periodontal disease in Chronic kidney disease may be severe even if low amount of biofilm is present. It is important that dentists know the most prevalent oral symptoms in the patient with Chronic kidney disease, as well as knowing that the periodontal condition of this patient should be carefully supervised.